Durability of Humoral Immune Responses to SARS-CoV-2 in Citizens of Ariano Irpino (Campania, Italy): A Longitudinal Observational Study With an 11.5-Month Follow-Up - Coppola, Annachiara; Buonerba, Carlo; Cardinale, Davide; Lo Conte, Gabriella; Sansone, Donato; Rofrano, Giuseppe; De Vita, Sabato; Morgante, Maria; Triassi, Maria; Atripaldi, Luigi; Brambilla, Gianfranco; Sabatino, Rocco; et al. (Frontiers in Public Health, 2021)
As of November 17, 2021, SARS-CoV-2 (Severe Acute Respiratory Syndrome CoronaVirus 2), the causative agent of COVID-19 (COronaVIrus Disease 19), has infected 250 million people worldwide, causing around five million deaths. Titers of anti-SARS-CoV-2 neutralizing antibodies were relatively stable for at least 9 months in a population-based study conducted in Wuhan, China, both in symptomatic and in asymptomatic individuals. In the mass screening campaign conducted in the town of Ariano Irpino (Avellino, Italy) in May, 2020, 5.7% (95% CI: 5.3-6-1) of the 13,444 asymptomatic citizens screened were positive for anti-nucleocapsid antibodies against SARS-CoV-2. Among these, 422 citizens were re-tested for anti SARS-CoV-2 antibodies in January, 2021 and/or in April, 2021 and enrolled in this longitudinal observational study. Median (interquartile range) age of the study cohort was 46 years (29–59), with 47 (11.1%) participants of minor age, while 217 (51.4%) participants were females. There was no evidence of re-infection in any of the subjects included. Presence of anti-nuclear antibodies antibodies (Elecysis, Roche) was reported in 95.7 and 93.7% of evaluable participants in January and April, 2021. Multiple logistic regression analysis used to explore associations between age, sex and seroprevalence showed that adults vs. minors had significantly lower odds of having anti-S1 antibodies (Biorad) both in January, 2021 and in April, 2021. Our findings showed that antibodies remained detectable at least 11.5 months after infection in >90% of never symptomatic cases. Further investigation is required to establish duration of immunity against SARS-CoV-2.